Soil macrofauna in spontaneous vegetation area in Jurubeba orchard Solanum paniculatum L. (Solanaceae) - Cabral, Maria Jéssica dos Santos (2021)
Soil fauna plays a major role in adjusting agricultural systems. Since the 1980s, studies have been carried out in Brazil as an indication of sustainable development of soil management. Has a great performance in the processes of decomposition, mineralization and humification of organic waste; immobilization and mobilization of macro and micronutrients. The objective was to compare the population of soil macrofauna in an area with spontaneous vegetation of jurubeba using different types of traps. This survey was carried out at the headquarters of the Arapiraca-AL Technological Agri-Food Complex, with an area of 240 m² using pitfall and TSBF traps, in an area of spontaneous planting of jurubeba (Solanum paniculatum L.). In the TSBF trap, four plots were used to count the macrofauna with the following depths: 0–5, 5-10, 10-15 and 15–20 cm deep. At the pitfall, five traps were installed on the ground that remained for five days. Taxonomic groups were identified in decreasing order of relative density at order and family level. Therefore, it can be observed in general that the orders of greatest prominence in relation to all categories were Hymenoptera (75%) and Coleoptera (58%), whereas the families that had the greatest amount were Formicidae with 176 and Gryllidae with 17.